2002
DOI: 10.4049/jimmunol.169.9.5036
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Association of CD45 with Detergent-Insoluble Microdomains in T Lymphocytes

Abstract: The receptor-like protein tyrosine phosphatase CD45 is essential for TCR signal transduction. Substrates of CD45 include the protein tyrosine kinases p56lck and p59fyn, both of which have been shown to be enriched in detergent-insoluble microdomains. Here we find that there is a cholesterol-dependent association between CD45 and the raft-associated protein linker for activation of T cells, suggesting that CD45 and linker for activation of T cells may colocalize in lipid rafts. Consistent with this observation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 49 publications
6
62
0
1
Order By: Relevance
“…Previous studies on whether CD45 translocates into LRs have yielded inconsistent results. The results of some studies have suggested that CD45 is excluded, while others have suggested that human leukemia cells and granulocytes transiently express CD45 in LRs (14,(31)(32)(33)(34). More recently, we observed that CD45 translocates into LRs in T cells from patients with SLE but not healthy controls (35).…”
Section: Discussionmentioning
confidence: 66%
“…Previous studies on whether CD45 translocates into LRs have yielded inconsistent results. The results of some studies have suggested that CD45 is excluded, while others have suggested that human leukemia cells and granulocytes transiently express CD45 in LRs (14,(31)(32)(33)(34). More recently, we observed that CD45 translocates into LRs in T cells from patients with SLE but not healthy controls (35).…”
Section: Discussionmentioning
confidence: 66%
“…Thus, the effect of Fcc-bearing immunotherapeutic agents may be significantly influenced by cells. Receptor-mediated modulation of antigen expression may also occur via the clustering and internalization of membrane microdomains, known as lipid rafts, that contain antigens such as CD20 and CD45 (Edmonds & Ostergaard, 2002). Finally, antibodies with an identical idiotype, that is specific for either the same or an overlapping epitope on a cell surface antigen, can display different internalization properties .…”
Section: The Differential Internalization Of Mabs By B-cll Cells In Vmentioning
confidence: 99%
“…In addition to factors that regulate the basal capacity or potential activity of CD45, CD45 protein tyrosine phosphatase activity and/or CD45 access to substrates may be further regulated following T cell activation (32,(52)(53)(54). These data suggest that the regulation of CD45 functional activity is likely to be complex and that different modes of regulation may be involved depending on the state of T cell activation and stage of development.…”
Section: Discussionmentioning
confidence: 97%
“…Initial reports in tumor cell lines suggested that raft-resident Lck was constitutively hyperphosphorylated due to the exclusion of CD45 from rafts and presumably due to raft targeting of Csk tyrosine kinase by PAG/cbp (30). However, more recent reports have suggested that a small percentage of CD45 has access to lipid raft domains and may regulate raft-resident Lck tyrosine phosphorylation (31,32). To clarify this issue in primary cells, we purified lipid raft and nonraft cell fractions from CD45 ϩ/Ϫ and CD45 Ϫ/Ϫ thymocytes by sucrose density gradient centrifugation.…”
Section: Differential Regulation Of Lck Y505 Phosphorylation In Lipidmentioning
confidence: 99%